Palliative Hypo-fractionated Radiotherapy for Locally Advanced Non-Small Cell Lung Cancer: A Feasibility Study - Dhaka, Saroj; Sihag, Rakesh Kumar; Saharan, Vidushi; Dhaka, Shankar Singh; Beniwal, Surender (Asian Pacific Journal of Cancer Care, 2024)
Objective: To assess the feasibility and potential benefits of palliative hypo-fractionated radiotherapy (HF-RT) compared to conventional fractionated radiotherapy (CF-RT) in patients with locally advanced non-small cell lung cancer (NSCLC). Materials and Methods: Fifty patients with unresectable stage III NSCLC received three cycles of neoadjuvant chemotherapy. After completion, 25 patients were randomized to receive HF-RT (17 Gy in 2 fractions, 8.5 Gy per fraction, on days 1 and 8) and 25 to CF-RT (50 Gy in 25 fractions, 2 Gy per fraction, administered daily for 5 weeks). Disease response was assessed using RECIST criteria at 1, 3, and 6 months, and overall survival was followed for up to 3 years. Result: No complete responses were observed in either group. Locoregional disease control rates were 18% in the HF-RT arm and 27% in the CF-RT arm (p > 0.05). Median survival was 10 months in the HF-RT arm and 12.5 months in the CF-RT arm, with no statistically significant difference. There was no significant difference in the grade of toxicities between the groups. Although a significant proportion of patients were lost to follow-up, among those followed, HF-RT showed a trend toward improved quality of life and shorter treatment duration. Conclusion: This feasibility study suggests that HF-RT may be a viable and potentially beneficial palliative option for locally advanced NSCLC patients, particularly those with poor performance status and a limited life expectancy. However, further research with larger cohorts and stricter follow-up is needed to confirm these preliminary findings and establish the true clinical benefits of this approach.